Community burden of hypertension and treatment patterns: An in-depth age predictor analysis: (The Rural Community Risk of Non-Communicable Disease Study - Nyive Phase I) - Osei-Yeboah, James; Owusu-Dabo, Ellis; Owiredu, William K. B. A.; Lokpo, Sylvester Yao; Agode, Francis Delali; Johnson, Beatrice Bella (PLOS ONE, 2021)
Background This study aimed to describe the burden, treatment patterns and, age threshold for predicting hypertension among rural adults in Nyive in the Ho Municipality of the Volta Region, Ghana. Methods A population-based cross-sectional study design was employed. A total of 417 adults aged 20 years and above were randomly selected from households within the Nyive community. The WHO STEPwise approach for non-communicable diseases risk factor surveillance (STEPS) instrument was used to obtain socio-demographic and clinical information including age, gender, educational background, marital status, and occupation as well as hypertension treatment information. Blood pressure was measured using standard methods. The risk of hypertension and the critical age at risk of hypertension was determined using binary logistic regression model and the receiver-operator characteristics (ROC) analysis. Results The direct and indirect age-standardized hypertension prevalence was higher in males (562.58/487.34 per 1000 residents) compared to the females (489.42/402.36 per 1000 residents). The risk of hypertension among the study population increased by 4.4% (2.9%-5.9% at 95% CI) for one year increase in age while the critical age at risk of hypertension was >39 years among females and >35 years among males. About 64(46.72%) of the hypertensive participants were not on treatment whereas only 42(30.66%) had their blood pressure controlled. Conclusion Rural hypertension is high among adults in Nyive. The critical age at risk of hypertension was lower among males. The estimated annual increase of risk of hypertension was 4.7% for females and 3.1% for males. High levels of undiagnosed and non-treatment of hypertension and low levels of blood pressure control exist among the rural folks.